Reevaluating immunization delays after red blood cell transfusion. Issue 9 (4th July 2019) - Zabeida, Alexandra; Lebel, Marc H.; Renaud, Christian; Cloutier, Marc; Robitaille, Nancy
Abstract : BACKGROUND: Current American and Canadian guidelines recommend delaying live vaccine immunization by 5 to 6 months after transfusion of red blood cells (RBCs) due to potential interference by serum antibodies. Due to lack of data, the recommendations may be unfounded and prevent valuable vaccination opportunities for children with frequent blood transfusions. The primary aim of this study was to determine measles, mumps, rubella (MMR) vaccine immunogenicity in patients chronically transfused with RBCs. A secondary aim was to quantify vaccine antibodies in RBC donations. STUDY DESIGN AND METHODS: MMR‐specific antibodies were quantified in 25 pediatric patients who received both doses of MMR vaccine while on a chronic RBC transfusion program (median, 6.6 years after vaccination). MMR antibodies were also quantified in 30 samples of supernatants from RBC donations. RESULTS: Immunity to each of the MMR components was 68% to 76%. In blood donors born before 1976 (pre‐MMR vaccine), 67% of MMR serologies in the supernatants of RBC donations were at the immune level versus 7% in blood donors born after 1976. CONCLUSION: This is the first study of the impact of RBC transfusions on MMR vaccine immunogenicity. Although lower than in the literature (immunity rates, ≥90%), the results show a high rate of immunogenicity of the MMR vaccine in chronically transfused patients. Additionally, results suggest that MMR antibody content in transfusions will continue to decrease with time. Weighing the risks and benefits of disease prevention in a vulnerable population, a reevaluation of immunization delays after RBC transfusions is called for.